Pengaruh Ekstrak Bengkuang (Pachyrhizus erosus) terhadap Kadar LDL Darah Tikus Putih (Rattus norvegicus) yang Diberi Diet Tinggi Lemak - Wijayanto, Rukmana; ., Suhanantyo; Setyawan, Novan Adi (Nexus Biomedika, 2013)
Background: Cardiovascular disease is the leading cause of disability and early death in the world. Increasing of blood LDL level is one risk factor for atherosclerosis that can develop into cardiovascular disease.Yam Bean contains isoflavones, flavonoids, phenols, and saponins which have hipolipidemic effect. This studyÂ aimed to determine the effect of Yam Bean (Pachyrhizus erosus) extract on blood LDL level of rats (Rattus norvegicus) with a high fat diet. Methods: This study was an experimental laboratory using post-test only with control group design. The subjects were 30 male Sprague Dawley (Rattus norvegicus) rats, two-months old with 130-240 grams of body weight (BW) that were divided into 6 groups randomly. Group KN was administered a normal diet, while K(+) was administered a high fat diet and simvastatin 0.18 mg/200 g BW/day. The group K(-) was administered aquadest and a high fat diet, while group P1, P2 and P3 were not only administered Yam Bean extract 70 mg, 140 mg and Â 210 mg/200 g BW/day, in a row, but also a high fat diet.Â High fat diet was cowâs brains which was administered 2 ml/200 g BW/day. Administration of Yam Bean extract, simvastatin, and high fat diet were performed for 21 days. Blood samples were taken on 22nd day at plexus preorbitalis. The LDL level was measured by CHOD-PAP method. Data were analyzed by One way ANOVA test and the Least Significance Difference (LSD) test (Î±=0.05). Results: The highest LDL level was on group K(-), followed by P1, P2, K(+), P3, while the lowest was KN. One way ANOVA test showed p=0.001. Whereas LSD test showed significant differences among each other groups (p<0.05) except between the group K(+) and P3 (p=0.174). Conclusion: Yam Bean extract showed a significant effect on blood LDL level of rats with a high fat diet. Increasing the dose of Yam Bean extract had positive correlation on decreasing blood LDL level of rats with a high fat diet. Keywords: Yam Bean extract, LDL, high fat dietÂ